Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker in Cervical Cancer: A Literature Review of Current Evidence - Ariefani, Salsabila; Rahmadhanita, Putri; Finalita, Floera (Journal of Islamic Medicine, 2026)
Background: The neutrophil-to-lymphocyte ratio (NLR) is a simple systemic inflammatory marker that reflects the balance between pro-tumor inflammation and anti-tumor immunity. Previous studies have shown that a high pre-treatment NLR is associated with poor survival outcomes and advanced clinical stage in cervical cancer. Objective: This review aims to evaluate the prognostic role of NLR and its impact on patient survival. Methods: A literature search was conducted for studies published between 2021-2026 using the PubMed/ MEDLINE database with predefined inclusion and exclusion criteria. A total of eight relevant articles were included in this review. Results: The included studies consistently demonstrated that a high pre-treatment NLR is an independent predictor of poor survival in patients with cervical cancer. Conclusion: NLR appears to be a promising prognostic biomarker for cervical cancer; however, the lack of standardized cut-off values limits its current clinical application.